การรับรู้ความสำคัญของปัจจัยที่มีอิทธิพลต่อความน่าเชื่อถือของเว็บไซต์สุขภาพ - กรุณา จีนถนอม (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
To study user perception on credibility factors of health-related websites and how the users search health information. The survey method is used for quantitative. Chi-square calculation is used for finding out the relation between demographic factors and credibility factors of health-related websites. T-test calculation was used for find out differences of average of health-related occupations and non-health-related occupations. The result shows that the first 10 factors enfluencing credibility of health-related websited are, (1) the source of the information can be found, (2) the information is up-to-date, (3) the website owners are reliable, (4) the sites are often updated, (5) the language used in the sites is easy to understand, (6) the writer names are specified, (7) the language spells correctly, (8) the sites have links to other reliable sites, (9) the information is categorized clearly and (10) there is contact person of the site. Chi-square calculation shows that age relates with importance of factors influencing the creditability of health-related websites. The sample uses google for searching health information instead of use the url of health-related websites. Finally, we have found that there are some demographic factors relate with type of health-information.